Imigração coreana em Aracaju/SE : uma construção da identidade - Souza, Marcelo Pereira (2019)
This dissertation deals with a study on the construction of a Korean identity, from a small group of Korean entrepreneurs who settled in the city of Aracaju / SE. Thus, we initially used the theoretical contributions to establish a possible convergence and / or divergence on the results of this immigration. Indeed, the results pointed out in this study corroborate the old order of migratory processes on the economic issue, given the relation of search for work, by the immigrant, but also reveals that there is a redirection about the immigration context, which follows with the same motivation of the initial displacement, the search for work. So soon, we take as an empirical field the business environment, whose "space" has revealed to us the construction of a cultural atmosphere that, in our eyes, goes to the encounter of a "territorialization". In this sense, networks play a role as explanatory models for the establishment of migration among Korean entrepreneurs, while proving the construction of a new territory and the strengthening of the group's cultural relationship. The symbolic, then, can be seen in relation to the structural relations of this group, as the form of organization, established hierarchy and power that was once seen as something impossible on the possession of the immigrant. For the development of this research, we use the case study method, seeking to highlight a particular case that can become generalized. In addition, the non-participant observation was fundamental to ascertain the logic of the information collected during the interviews, as well as to verify the theoretical thinking, in empirical terms, that are established around the identity construction of the entrepreneurs. Regarding the results of this research, we point out the trajectory of Korean immigrants as one of the influential elements of their identity processes, including for the construction of their business identity. In the businesses created, we identify the hierarchy established between them that besides defining roles, corroborates the order between the group and its relations, including for the strengthening of the group. However, business functions as conducive spaces for cultural diffusion, since Koreans live at work and for work.